Moral and Religious Values in the Animated Stories of the Prophets for Early Childhood on Youtube Channel - Iman, Yasminne Nur Annisa; Diana, Raden Rachmy (Jurnal Pendidikan Raudhatul Athfal, 2024)
Early childhood (0-6 years) is in the golden age of development, where they are very responsive to the environment. At this stage, children are in preconventional moral reasoning and absorb information very easily. The inculcation of moral and religious values is very important at this age and can be done through a variety of media, including animated films. This study aims to explore and analyze animated content on YouTube, especially the stories of the Prophets, to assess its effectiveness in instilling moral and religious values in early childhood. This research uses an analytical descriptive methodology with a qualitative approach, through observation and documentation of content from the KABI-The Story of the Prophet's Example YouTube channel. YouTube as a popular platform offers easy access to educational content that can support children's development if accompanied by parental supervision. This channel presents inspirational stories that contain moral and religious values. The results of the study show that the animated content is effective in instilling Islamic religious and moral values in early childhood, helping them develop moral principles and religious understanding from an early age. This study emphasizes the importance of wise use of digital media to support early childhood education.